ANALYSIS OF ARABIC CLASS 2 HIGH SCHOOL LEARNING BOOKS PUBLISHED BY THE MINISTRY OF RELIGION IN 2020 - Nurhuda Abdillah (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research aims to reveal the quality of the Arabic language teaching book for the second secondary grade of the Indonesian Ministry of Religious Affairs in 2020, in the light of the Arabic Language Curriculum and Teaching Methods book by Saad Ali Zayer and Iman Ismail Ayez and the validity of its use among second-grade secondary students in schools in Indonesia using the criteria for preparing a good book. In writing this research, the study used the descriptive analytical method. As for the scientific method used in it, it is a qualitative method. After carrying out the analysis process, the study found the validity of using the Arabic language book for the second grade of secondary school of the Indonesian Ministry of Religious Affairs in 2020 for students of the second grade of secondary school, and it is a good book as it is presented in a scientific way, but there is a slight error in adjusting the shape of some The words.